Problem-Based Learning Model as an Approach to Learning in Islamic Religious Education - Muhlasin, Ahmad; Ikhsan, I (Al'ulum Jurnal Pendidikan Islam, 2026)
This article examines Problem Based Learning (PBL) as a relevant learning approach for Islamic Education (PAI) through a literature study. The study was conducted by collecting and analyzing scientific literature related to PBL and Islamic education, then synthesized descriptively based on four research objectives: concepts and basic principles of PBL, characteristics of PBL relevant for PAI, recent research findings, and theoretical and practical implications of PBL implementation. The results show that PBL emphasizes authentic problem-based learning, learner-centered, investigative, collaborative, and reflective. PBL characteristics are in line with Islamic education values, including critical thinking, deliberation, contextualization of religious values, and character development. A synthesis of recent research findings shows the consistent contribution of PBL in improving critical thinking skills, creativity, active engagement, concept understanding, and collaboration and communication skills.